Дослідження принципів, моделей та методів парадигми менеджменту наукових даних FAIR для аналізу метаданих BIG DATA - Рогушина, Ю.В.; Гришанова, І.Ю. (Проблеми програмування, 2021)
Розглянуто базові принципи, моделі та методи парадигми менеджменту наукових даних FAIR (Findable, Accessible, Interoperable, Reusable як окремого випадку великих даних (Big Data), яка орієнтована на повторне використання результатів наукових досліджень. Проаналізовано, як властивості даних FAIR сприяють уніфікації й об’єднанню наукової інфраструктури у парадигмі відкритої науки. Запропоновано методи та програмні засоби, за допомогою яких властивості даних FAIR можуть відтворюватися у семантично розмічених Wiki-ресурсах, що побудовані на основі Semantic MediaWiki. In this research work we considere the basic principles, models and methods of the FAIR (Findable, Accessible, Interoperable, Reusable) scientific data management paradigm as a separate case of Big Data. This paradigm is focused on the reuse of scientific research results.Basic principles of FAIR apply to three types of entities: data (or any digital object), metadata (information about this digital object) and infrastructure. Information on various projects, initiatives and communities working on solving the problems of scientific data and their metadata integration is examined.
We analyze how the properties of FAIR data contribute to the unification and integration of the scientific infrastructure in the paradigm of open science, which is based on free access to research results and open data.